The Changing Role of Health Care Professionals in Nursing Homes: A Systematic Literature Review of a Decade of Change - van Stenis, Arend R.; van Wingerden, Jessica; Kolkhuis Tanke, Isolde (Frontiers in Psychology, 2017)
Although the role of health care professionals is known to have changed over the last years, few formal efforts have been made to examine this change through means of a scientific review. Therefore, the goal of this paper was to investigate the changing role of health care professionals in nursing homes, as well as the conditions that make this change possible. A systematic review of health care literature published in the last decade (2007 – 2017) was utilized to address these goals. Our findings suggest that although health care in nursing homes is shifting from task-oriented care to relation-oriented care (e.g., through an increased focus on patient dignity), various obstacles (e.g., negative self-image, work pressure, and a lack of developmental opportunities), needs (e.g., shared values, personal development, personal empowerment, team development, and demonstrating expertise), and competences (e.g., communication skills, attentiveness, negotiation skills, flexibility, teamwork, expertise, and coaching and leadership skills) still need to be addressed in order to successfully facilitate this change. As such, this paper provides various implications for health care research, health care institutions, practitioners, HR professionals and managers, and occupational health research.